Japanese/Korean popular culture in Kuwait and Singapore: Resistance and conservatism. Issue 1 (7th March 2023) - Botz-Bornstein, Thorsten
In 2017, I launched a survey on the importance of Japanese and Korean popular cultures in Kuwait. I discovered a paradoxical pattern of resistance to the East through the adherence to another eastern culture. I wanted to examine how other non-western countries handle 'Japanese culture' in comparison and decided to adopt Singapore as a sample case. Both Kuwaiti and Singaporean students stress the differences between Japan/Korea and their own country, but also insist on similarities. In both surveys there is a strong emphasis on ethics. Both are impressed by the Japanese politeness and their capacity to organize life, and most reasonings evolve around the theme of 'conservatism'. Singaporean students, when asked about Japan and Korea, point to conservative patterns predating what they perceive as the Americanization of Asia. The positive values located in this part of East Asia correspond with precisely those values that Kuwaiti students (as well as Singaporean Muslim students) single out as particularly compatible with Islamic mindsets. In both countries, respondents see Korea/Japan as the 'real' Confucian/Muslim nations harking back to more pristine values. Negative evaluations, for example of hallyu as a soft power for Korean economic interest, are almost absent.